Open Text Form in Sherko Bekas's Poetic Experience - Mohammed Qadir Mahmood; Hemdad Hussen Bakir (Zanco Journal of Humanity Sciences)
Open text is a new form of Kurdish poetry, carrying the characteristics of literary genres and maintaining the balance between these genres in the text. It is the combination of genres within a text in a new poetic form. It is working to find and develop common ground between genres, since narrative takes a large space in the poetic text and complements mental expressions. The combination of poetry and narrative in an open text directly creates metaphors, metaphors and artistic images and produces a different form of poetry. The poet Sherko Bekas also played a role in the emergence of this new form of poetry and dealt with language in an accurate and creative way. This has created a delicate melody inside the poem and enhanced the poetry of the text.